Innovative changes in personnel management (Economics and region, 2023)
This article includes the systematization and generalization of modern research in the field of innovative technologies in personnel management. The article also develops the interpretation of the essence and content of the concept of innovation and innovative technologies in personnel management and analyzes their application at foreign enterprises. These studies make it possible to analyze the degree of relevance of innovative technologies in personnel management and subsequently draw conclusions about their implementation at Ukrainian enterprises. Based on the analyzed sources, the main HR trends presented on the market, the study and implementation of which increase the efficiency and effectiveness of the work of employees, and a list of innovative technologies in personnel management are outlined. The article highlights the main goals of implementing innovative technologies in personnel management, shows their leading role and place among the key factors of the organization's internal environment. Emphasizes attention on modern business trends: density of markets, competition for customers, competition for quality; simplification and flexibility of structures; demand for independence and responsibility at the level of employees; competitive advantage in the area of intangible assets; in particular, conviction that innovation, change leadership and flexibility are the basis of organizational success. Emphasizes the superimportance of optimizing all components of personnel support: interaction between managers and workers; recruitment, training and promotion of personnel; assessment of work results and incentives; creation and maintenance of proper relations between employees; taking into account most of the components of their motivation, in particular, a flexible work schedule. The article also reveals an up-to-date method of paying workers, which is safe and convenient. Since the task of this article is the systematization and analysis of current research in the field of personnel management, the purpose of this publication is to popularize and encourage already existing and world-famous trends.
Keywords: innovations; innovative technologies; management; personnel; trends; flexibility; HR trends